Body mass index categories and attained height in Portuguese adults - Rosário, Rafaela (2018)
Objective: To analyze the associations between height and BMI categories in a Portuguese representative sample. Methods: This is a cross-sectional study with a representative sample of 32,644 Portuguese adults (52.4% females). Sociodemographic and lifestyle characteristics were obtained along with self-reported height and weight. We performed generalized linear models to assess the differences in attained height across BMI categories; analyses were adjusted for age, gender, education, family income per month, proxy reporting information, dietary patterns, and smoking. Results: BMI categories included underweight and normal weight (46.4%), overweight (37.6%), obese class I and II (15.2%), and obese class III (0.8%). Adults with normal weight had a significantly higher height (females +7 cm and males +5 cm) when compared to obese class III. As BMI categories increased, height decreased. In females and males, after adjusting for confounders, estimates of attained height decreased when compared to the unadjusted model (beta = -0.049, 95% CI = -0.050; -0.049 and beta = -0.030, 95% CI = -0.031; -0.029, respectively), although they remained still significant. Conclusion: Our results suggest a significant difference in attained height between BMI categories. Future intervention programs aiming at preventing overweight and obesity should monitor sociodemographic, health and environmental conditions that affect attained height potential.